The Influence of Leadership on Lecturer Performance at University in Makassar City - Megawaty Megawaty (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
This research aims to determine and analyze the influence of leadership on lecturer performance at state universities and private universities in Makassar city. The method used is quantitative, with multiple linear regression analysis using SPSS 22 as a processing data tool. The total sample in this study was 60, consisting of 30 lecturers at a state university and 30 lecturers at a private university. The research results in the conclusion in this study leadership which indicators (clarity of vision and mission, achievement of vision and mission, optimism, confidence, agility, setting an example, and delegation of authority) have a positive and significant impact partial and simultaneous test. The work of lecturers at state and private universities in the three teaching areas of education, research and publication, and community service is closely linked to making higher education more competitive. Leadership abilities in developing competence and commitment also heavily impact lecturer performance. Leadership who can set an example, act swiftly, delegate authority well, and maintain a high degree of optimism can enhance professor performance in public and private colleges.